Structural, magnetic and dielectric properties of BaFe2Se3 crystals. (3rd June 2019) - Liu, Xiang; Ma, Chao; Hou, Chuangming; Chen, Qiaoling; Sinclair, Ryan; Zhou, Haidong; Yin, Yuewei; Li, Xiaoguang
Abstract: Recently, theoretical studies have indicated that BaFe2 Se3 may host a ferrielectric polarization and an uncompensated ferroelectricity driven by the exchange striction in its magnetic block order. Here, structural, magnetic, electrical transport, dielectric, and magneto-dielectric properties in the BaFe2 Se3 single crystals were systematically investigated. Below 320 K, BaFe2 Se3 is a semiconductor, and the thermal activated transport processes with different activation energies were used to describe the conductivities in high and low temperature ranges. Magnetization measurements show a crossover from a short-range antiferromagnetic correlation to a long-range antiferromagnetic order at around 230 K and another antiferromagnetic transition at 150 K. The dielectric constant can be changed by about 6% in a magnetic field of 8 T. However, the ferrielectric characteristics of BaFe2 Se3 are difficult to be fully verified by electric polarization and dielectric measurements, which may be related to the quite narrow energy gap and low resistivity.